In the Shadow of the Prophet : The Struggle for the Soul of Islam - Viorst, Milton (New York Westview Press, 2001)
"Illuminates the complex struggle to reconcile the Muslim community's fierce determination to live by traditional Islamic law and beliefs with the desire for economic and political power in today's world."--Cover.
Include Notes, Bibliography and Index
Keywords: Islamic countries -- Politics and government -- Islam--Essence, genius, nature